Intracellular dry mass density increases under growth-induced pressure [version 2; peer review: 1 approved, 2 approved with reservations] - Baptiste Alric; Hyojun Kim; Julien Roul; Nolan Chan; Morgan Delarue (Open Research Europe)
Cells that proliferate in confined environments develop mechanical compressive stress, referred to as growth-induced pressure, which inhibits growth and division across various organisms. Recent studies have shown that in these confined spaces, the diffusivity of intracellular nanoparticles decreases. However, the physical mechanisms behind this reduction remain unclear. In this study, we use quantitative phase imaging to measure the refractive index and dry mass density of Saccharomyces cerevisiae cells proliferating under confinement in a microfluidic bioreactor. Our results indicate that the observed decrease in diffusivity could be attributed to the intracellular accumulation of macromolecules. Furthermore, the linear scaling between cell content and growth-induced pressure suggests that the concentrations of macromolecules and osmolytes are maintained proportionally under such pressure in S. cerevisiae.